Managing Public Debt-Formulating Strategies and Strengthening Institutional Capacity. (Policy Papers; Policy Paper ;, 2009)
In May 2007, the IMF and World Bank Boards discussed the paper "Strengthening Debt Management Practices: Lessons from Country Experiences and Issues Going Forward". In those discussions, the Boards of both institutions endorsed a public debt management (PDM) work program that was particularly focused on strengthening frameworks and capacity in low-income countries (LICs). This comprised three main elements: (i) develop a toolkit to help LICs formulate an effective Medium-Term Debt Management Strategy (MTDS) and apply it in 4-6 countries a year; (ii) undertake debt management performance assessments; and (iii) continue the provision of debt management and domestic market development technical assistance (TA) and advisory services to middle-income countries (MICs). This paper is a response to the Boards' request for an update on the development and implementation of that work program. Developing a Medium-Term Debt Management Strategy (MTDS)- Guidance Note for Country Authorities Debt Management Performance Assessment Tool (DEMPA) Developing a Medium Term Debt Management Strategy: User Guide and Analytical Tool - In March 2009, the Executive Boards of the World Bank and the IMF endorsed the Medium Term Debt Management Strategy (MTDS) Framework developed by IMF and World Bank staff to help countries elaborate effective debt management strategies. The MTDS framework and toolkit comprises two elements: An operational guidance note (GN) and a spreadsheet-based analytical tool (AT). The GN provides practical guidance on the process of developing an effective MTDS, describing each step involved, while the AT provides quantitative analysis to guide the MTDS decision-making process.